Diversity of Light Sensing Molecules and Their Expression During the Embryogenesis of the Cuttlefish (Sepia officinalis) - Bonadè, Morgane; Ogura, Atsushi; Corre, Erwan; Bassaglia, Yann; Bonnaud-Ponticelli, Laure (Frontiers in Physiology, 2020)
Eyes morphologies may differ but those differences are not reflected at the molecular level. Indeed, the ability to perceive light is thought to come from the same conserved gene families: opsins and cryptochromes. Even though cuttlefish (Cephalopoda) are known for their visually guided behaviors, there is a lack of data about the different opsins and cryptochromes orthologs represented in the genome and their expressions. Here we studied the evolutionary history of opsins, cryptochromes but also visual arrestins in molluscs with an emphasis on cephalopods. We identified 6 opsins, 2 cryptochromes and 1 visual arrestin in Sepia officinalis and we showed these families undergo several duplication events in Mollusca: one duplication in the arrestin family and two in the opsin family. In cuttlefish, we studied the temporal expression of these genes in the eyes of embryos from stage 23 to hatching and their expression in two extraocular tissues, skin and central nervous system (CNS = brain + optic lobes). We showed in embryos that some of these genes (Sof_CRY6, Sof_reti-1, Sof_reti-2, Sof_r-opsin1 and Sof_v-arr) are expressed in the eyes and not in the skin or CNS. By looking at a juvenile and an adult S. officinalis, it seems that some of these genes (Sof_r-opsin1 and Sof_reti1) are used for light detection in these extraocular tissues but that they set-up later in development than in the eyes. We also showed that their expression (except for Sof_CRY6) undergoes an increase in the eyes from stage 25 to 28 thus confirming their role in the ability of the cuttlefish embryos to perceive light through the egg capsule. This study raises the question of the role of Sof_CRY6 in the developing eyes in cuttlefish embryos and the role and localization of xenopsins and r-opsin2 . Consequently, the diversity of molecular actors involved in light detection both in the eyes and extraocular tissues is higher than previsously known. These results open the way for studying new molecules such as those of the signal transduction cascade.